Impacts of Indonesian National Education Policy in Responses to Covid-19 Pandemic on Hindu Faith-Based Schools Student Assessment - Suryanto Suryanto (IAHN-TP Palangka Raya, 2022)
The Covid-19 outbreak caused significant changes in Indonesian education policy, especially on the national assessment and examination system for the primary and secondary levels. The purpose of this article is to describe the national education policy taken by the Indonesian government in response to Covid-19 and its impact on the student assessment and government recognition of Hindu faith-based schools known as Widya Pasraman. The data were collected through field research observation, interviews, and analysis of legal documents on national religious education policy. The data analysis is done through the qualitative data analysis method. The results of this study show that policy changes in the national exam system in response to Covid-19 have a significant impact on the institutional recognition process of Hindu faith-based religious education schools and the assessment of learning outcomes in Widya Pasraman. The pandemic complicated the bureaucratic processes of the development of Widya Pasraman institution as the implementation of mono-religious education policy model taken by the government of Indonesia.